Critical analysis of the Fall of Fiqa – Yi Democrat Azerbaijan, (Iran, 1946) - Khandagh, Najleh (Advances in Social Sciences Research Journal, 2015)
This article examines the Firqa – Yi Democrat Azerbaijan an autonomous movement, supported popularly and caused by the historical circumstances of Reza Shah‘s dictatorship (1921-1941) and subsequence central government pressure which culminated in the rejection by the Majlis of Pishavari‘s credentials. Despite increasing governmental pressure the movement became self - governing and was supported by the Soviet Union though opposed by America and Britain, which opposition ultimately aided its downfall, though not before a considerable number of beneficial reforms had been carried out in the province. This field has been hitherto unexplored due to the need to know Azari Turkish. Persian and English, and because in the Pahlavi period investigation was difficult, materials scarce and interviews very dangerous. Only after the fall of the Shah has there been the chance to undertake original work and publish conclusions. with the international reaction, the role of the United Nations, and that of the Prime Minister, Qavam, who concluded agreements with the Firqa - Yi Democrat leader and the USSR. The successful pressure from the West and the U.S. on the central government to crush the movement and the international agreement between America and the USSR, are analyzed. Finally, the causes of failures of the movement and the subsequent ban on all political parties